Analysis of Water Quality Correlation with the Immune Response of Litopenaeus vannamei in Probolinggo, East Java - Putra, Andhika Farras Rahardian; Suryanto Hertika, Asus Maizar; Maimunah, Yunita (International Journal of Marine Engineering Innovation and Research, 2025)
Whiteleg shrimp (Litopenaeus vannamei) is an important fishery commodity in Indonesia, but its success is strongly influenced by water quality, which can impact the health and immune system of the shrimp. Poor water quality has the potential to induce physiological stress in vannamei shrimp and disrupt their immune system, necessitating research to optimize water quality in shrimp aquaculture. This reseacrh employed a quantitative descriptive method to analyze data obtained through simple random sampling in vannamei shrimp ponds in Probolinggo, East Java. The water quality parameters measured included temperature, pH, DO, TSS, TDS, salinity, ammonia, and nitrate, while immune parameters such as THC, DHC, and phagocytosis activity were assessed. Canonical Correspondence Analysis (CCA) was used to analyze the relationship between water quality and immune parameters. The results indicated a significant influence of water quality on the immune parameters of the shrimp, providing valuable insights for more effective pond management. The findings of this research are expected to assist shrimp farmers in improving water quality and the immune system of vannamei shrimp, thereby reducing stress and enhancing productivity in sustainable shrimp aquaculture.